Qualidade de vida e sobrecarga do cuidador familiar de mulheres em tratamento do câncer de mama - Santos, Sônya Cristina Plácido dos (2014)
Introduction: The experience of cancer provides suffering both the patient and the family member responsible for providing care. Objectives: To assess the Quality of Life of Family Caregivers of women in treatment of breast cancer and its association with sociodemographic data of the caregiver and clinical data of women; to assess the burden of family caregivers of women in treatment for breast cancer and examine its relationship to quality of life of the caregiver. Methods: This is an observational study conducted at Hospital Santa Rita (HSRC), whose sample consisted of 62 family caregivers. Where used the SF-36 questionnaire (Study36-Item Short-Form Health Survey) to evaluate the Quality of Life and the Zarit Burden Interview Scale (ZBI) to measure the overhead. We used the Kruskal Wallis test to assess the association of scores of Quality of Life with the studied variables, the chi-square test to assess the variables associated with the presence of the caregiver burden and the Mann-Whitney test to verify the relationship between the presence of overhead and scores of Quality of Life. Results: There where predominantly female, daughters/sons, being married, aged between 46-55 years. There were statistical significance (p <0.05) between being female and the Functional Capacity, Vitality, Social Functioning, and Mental Health domains; between age and Physical Aspects domain; between religion and Functional Capacity and General Health domains; between place of origin and Pain and Vitality domains; between family income and domain Emotional Aspects; between occupation and Functional Capacity Mental Health and Vitality domains. Among the caregivers, 37.1% had moderate to severe overload. There were found a statistically significant difference between caregivers with and without overhead in all dimensions of Quality of Life instrument. Conclusion: Quality of life of caregivers of women undergoing treatment for breast cancer is influenced by sociodemographic factors. These results further support that strengthen actions aimed at family caregivers, since this population lacks direction and appropriate professional home monitoring.